Getting started with Greenplum for big data analytics : a hands-on guide on how to execute an analytics project from conceptualization to operationalization using Greenplum /: a hands-on guide on how to execute an analytics project from conceptualization to operationalization using Greenplum. (2013) - Unknown
No abstract available